Some helminth parasites of Nevada bullfrogs, Rana catesbiana Shaw - Babero, Bert B.; Golling, Katharina (Revista de Biología Tropical, 1973)
In a survey of tbe helminth parasites of bullfrogs in the area of Ash Meadows, Nevada, 12 species comprising 7 genera were collected. The helminths recovered are as follows: (Nematoda) Eustrongylides wenrichi, Spironoura calesbianae and Abbreviata sp.; (Trematoda) Langeronia provitellaria, Glypthelmins quieta, G. subtropica, G. proximus, G. sera, Haematoloechus buttensis, H, breviplexus, and H. parviplexus; (Cestoda) Ophiotaenia magna. Brief discussions on each of the preceding parasites are presented. Eustrongylides wenrichi, in its encystment in the musculature, viscera, and egg-mass, was found to be highly pathogenic to bullfrogs.